Fiber Cyclone Palm Oil Mill Capacity 45 Tons/Hour - Istianto Budhi Rahardja; Juni Afriani; Ahdiat Leksi Siregar; Daruki Daruki; Deni Almanda; Firmansyah Firmansyah; Anwar Ilmar Ramadhan; Mohd Hamisa Abdul Hamid (Journal of Applied Sciences and Advanced Technology, 2022)
The processing of Fresh Fruit Bunches into crude palm oil and palm kernel can be done by starting to boil the Fresh Fruit Bunches until they are ripe, after the Fresh Fruit Bunches are ripe, then separate the bunches from the fiber by going through the slaughtering process, after which the fiber is then chopped and immediately pressed so that the oil comes out. After the oil and fiber are separated, the fiber will go to the fiber cyclone. Fiber cyclone is a device located at the solids station, the main function of the fiber cyclone is to separate the nut and fiber by sucking the fiber using air, through the ducting column and will exit through the air lock and then go to the boiler to be used as fuel. The fiber cyclone has a speed of 10.08 m/s for the velocity box, a vertical column of 6.86 m/s, and 8.57 m/s for the horizontal column. Fiber cyclone has 1 loss point for kernel, what is analyzed is the output of fiber cyclone which is fiber taken from air lock, the standard loss for fiber cyclone is 0.10%.